Performance of partial nitritation - microfiltration-anammox (PN-MF-A) process with enhanced system stability via in-between membrane filtration for sludge anaerobic reject water treatment. Issue 5 (October 2021) - Ding, Jianning; Gong, Hui; Wang, Shunyu; Xu, You; Xu, Enhui; Yang, Dianhai; Gu, Guowei; Dai, Xiaohu
Abstract: Conventional two stages partial nitritation - anammox (C-PN-A) process is an energy-efficient and sustainable technology for sludge anaerobic reject water treatment, which has usually reported with system instability and limited total nitrogen removal rate (TNRR). Overgrowth of flocculent heterotrophic bacteria in Anammox stage induced negative effects on anammox activity. To prevent direct transportation of flocculent heterotrophic bacteria from PN stage to Anammox stage, novel partial nitritation - microfiltration - anammox (PN-MF-A) process was proposed in this research. More stabilized operation was achieved for PN-MF-A process with higher TNRR of 0.80–0.96 kgN/(m 3 ·d) than C-PN-A of 0.53–0.57 kgN/(m 3 ·d). There was a great deal of overlaps in genus level of microbial community structure between floc sludge in PN and Anammox reactor, indicating flocculent microorganism in anammox reactor came from PN reactor, which probably could survive both in aerobic and anaerobic conditions. The in-between membrane of PN-MF-A process removed nearly 100% suspended solid (SS) and 15.31–37.83% COD, accordingly preventing the microorganism transfer from PN stage to Anammox stage and reducing the inhibitory effects of the anaerobic reject water on the anammox. Although same inoculum was used for the two sets anammox reactors, genus level shift was observed that Candidatus Brocadia (abundance 10%) in C-PN-A and Candidatus Kuenenia (1.4%) in PN-MF-A process. Higher anammox activity in PN-MF-A process was illustrated with less abundance (1.4%) than C-PN-A process. This research initially illustrated feasibility and advantages of proposed novel PN-MF-A process for high inhibitory reject water treatment. Graphical Abstract: ga1 Highlights: Novel partial nitritation - microfiltration - anammox (PN-MF-A) process was proposed. More stabilized operation was achieved for PN-MF-A with higher TNRR of 0.80–0.96 kgN/(m 3 d). The in-between membrane removed nearly 100% suspended solid and 15.31–37.83% COD. PN-MF-A prevented the microorganism transfer from PN stage to Anammox stage and reducing the inhibitory effects. Although same inoculum was used, anammox genus level shift was observed.